2011
DOI: 10.1111/j.1600-079x.2011.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease: pathological mechanisms and the beneficial role of melatonin

Abstract: :  Alzheimer’s disease (AD) is a highly complex neurodegenerative disorder of the aged that has multiple factors which contribute to its etiology in terms of initiation and progression. This review summarizes these diverse aspects of this form of dementia. Several hypotheses, often with overlapping features, have been formulated to explain this debilitating condition. Perhaps the best‐known hypothesis to explain AD is that which involves the role of the accumulation of amyloid‐β peptide in the brain. Other the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
203
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(206 citation statements)
references
References 481 publications
(579 reference statements)
1
203
0
2
Order By: Relevance
“…63 La administración de esta indolamina a sujetos que padecen EA causa una mejoría en los trastornos de los ritmos circadianos [64][65][66] así como una reducción en la disfunción cognitiva. 67 Los estudios preclínicos apoyan este concepto ya que la MEL actúa como un captador de radicales libres y por lo tanto reduce el estrés oxidativo y la apoptosis.…”
Section: La Melatonina Como Una Alternativa En El Tratamiento De Las unclassified
“…63 La administración de esta indolamina a sujetos que padecen EA causa una mejoría en los trastornos de los ritmos circadianos [64][65][66] así como una reducción en la disfunción cognitiva. 67 Los estudios preclínicos apoyan este concepto ya que la MEL actúa como un captador de radicales libres y por lo tanto reduce el estrés oxidativo y la apoptosis.…”
Section: La Melatonina Como Una Alternativa En El Tratamiento De Las unclassified
“…In addition to inhibiting mitochondrial respiratory complex activities in AD patients, disturbances in mitochondrial dynamics have also been demonstrated. This includes disturbances in mitochondrial structure, impairment of dynamin -related peptide (Drp1) and imbalances in fission and fusion, with consequent neuronal damage and synaptic loss [27]. Significant disturbances of mitochondrial proteins and lipids also occur following intramitochondrial accumulation of Aβ, which in turn causes functional impairment of mitochondria in AD [26].…”
Section: Amyloid β Peptide and Mitochondrial Interaction As Triggerinmentioning
confidence: 99%
“…learning and memory) impairment [61] and is associated with Ab [62]. Rosales-Corral et al [63] suggested that melatonin could present multiple potential functions that correspond to several possible pathological mechanisms including the cholinergic hypothesis. Moreover, 'melatoninergic' or melatonin-type drugs may relieve dementia-related cognitive deficits and other syndromes [64,65].…”
Section: Biological Insights Into Small Moleculementioning
confidence: 99%